Dissociação dependente de voltagem da Tityustoxina do sítio de ligação em canais de sódio - Fabiana Vasconcelos Campos (2002)
Voltage-dependent channeles are membrane proteins that suffer conformational changes as result of variations on membrane potential. The ion Na+ fluxes into the cells through these channels. In the resting state they are closed. With a depolarization they pass quickly through an open state and go to the inactivated state. Voltage-dependent sodium channels present on GH3 cells membrane were studied using their interaction with tityustoxina (Tstx), an alpha toxin from scorpion Titys serrulatus. These toxins bind to receptor site 3 of the sodium channels in a voltage-dependent way, modifying the inactivation process. Site 3 is on the extracellular surface of the sodium channel and involves structures related with the activation process. The effects of the tityustoxina on inactivation were studied using the kinetics of the decay of inward an outward sodium currents. In the presence of toxin, the kinetics of both currents was slower. Toxin-channel interaction was stable during depolarizing pulses to 0 mV, depolarizing pulses, which means that the voltage dependence of the binding is not related to suggesting that the voltage-dependence of dissociation is independent of the activation process. However, higher depolarizing pulses ( +100 to +200 mV) were able to remove the toxin of its binding site. The rate of dissociation depended on the amplitude, duration and number of pulses applied. There was also a pended of bath temperature. We suggest that the mechanism of voltage-dependent dissociation of the tityustoxina is related to the conformational changes of the a voltage sensor of the channel during high depolarization.